1981
DOI: 10.1136/thx.36.8.605
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic-pituitary dysfunction in respiratory hypoxia.

Abstract: Eight hypoxic male patients with stable chronic obstructive airways disease were submitted for combined anterior pituitary function testing. All subjects showed normal growth hormone and essentially normal cortisol responses to adequate hypoglycaemia, two subjects showed delayed responses of thyroid stimulating hormone to administered thyrotrophin releasing hormone and all had basal prolactin levels within normal limits. Basal levels of luteinising hormone were significantly lower than in the group of age-matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
1
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 17 publications
2
55
1
1
Order By: Relevance
“…Previous studies of the primary defect in disease-induced gonadal endocrine failure have yieided inconsistent results with respect to the mechanisms re3consible (9,(26)(27)(28)(29)(30). Our findings of low free testosterolic levels and concurrently elevated gonadotrophins in debilitated lung cancer patients are suggestive of a primary gonadal dysfunction.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Previous studies of the primary defect in disease-induced gonadal endocrine failure have yieided inconsistent results with respect to the mechanisms re3consible (9,(26)(27)(28)(29)(30). Our findings of low free testosterolic levels and concurrently elevated gonadotrophins in debilitated lung cancer patients are suggestive of a primary gonadal dysfunction.…”
Section: Discussionsupporting
confidence: 45%
“…Hypothalamic-pituitary-gonadal axis failure may be a result of various pathological states in several organ systems. In numerous studies, male patients with lung cancer (2-7), patients undergoing cyclic chemotherapy for lung cancer ( I , 2), and patients with chronic hypoxic disease (2,(8)(9)(10)(11)(12)) have all been shown to display these features. Although the 'fatigue syndrome' may be responsible for the gonadal endocrine dysfunction in these patients (13, 14), the mechanisms responsible for this phenomenon have not been resolved.…”
mentioning
confidence: 99%
“…Spartt et al (1992) suggested that primary hypogonadism occurs in acute illness. Second hypogonadism in mean with critical illness, surgery (Wang et al 1978) or respiratory failure (Semple et al 1981) is attributed to hypogonadotropism. Reproductive axis suppression in acute illness is related to disease severity (Dong et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In 1981, Semple et al, reported that hypoxia induced during chronic obstructive airway diseases in humans can lead to alterations of the hypothalamic-pituitary function, particularly in the pituitary-testicular axis (18), although these findings were subsequently questioned in a study by Banks et al (19). Studies in rats and pikas and ewes, exposed to altitude mediate reduced oxygen breathing suggested that hypoxic stress increases release of ACTH via cAMP (4,20).…”
Section: Figure 1 Immunohistochemical Staining Of Tissue Sections: (mentioning
confidence: 95%